Implementation Analysis Of Stunting Prevention And Reduction Policies Using The Health In All Policies Framework In Samarinda City - Muhammad Rafli Aidillah; Dwi Ida Puspitasari (Jurnal Kesehatan Manarang, 2025)
Stunting represents a complex public health challenge that leads to impaired physical growth and cognitive development among children. In Samarinda City, the prevalence of stunting remains high at 25.3%. To address this issue, the local government has implemented a range of preventive and control strategies through both sensitive and specific interventions integrated within regional programs and activities. This study examines the implementation of stunting prevention and control policies across sectors in Samarinda City using a qualitative case study design. Research participants were purposively selected based on their involvement and experience in stunting-related programs, resulting in 14 informants representing eight key agencies. Data analysis involved a systematic process of transcription, familiarization, coding, categorization, thematic identification, and synthesis of findings. To ensure research validity, the study applied triangulation across data sources, researchers, theories, and methodological approaches. The findings show that policymakers have initiated multisectoral collaboration by establishing the Stunting Reduction Acceleration Team. However, institutions still coordinate in a procedural and fragmented manner. Data managers continue to face challenges due to the unsynchronized nature of information systems, which hinders evidence-based planning. Despite these obstacles, policymakers have introduced adaptive innovations, such as local food supplementation programs, adolescent health education, and community-based initiatives, that reflect Samarinda’s growing commitment to integrating health considerations into broader governance structures. These actions demonstrate emerging institutional learning and adaptive governance consistent with HiAP principles. In conclusion, policymakers in Samarinda City have advanced cross-sectoral collaboration and localized innovation in stunting prevention and reduction. However, weak data integration and institutional silos continue to limit progress. To realize the HiAP vision for equitable and sustainable health outcomes, it is essential to strengthen coordination mechanisms, establish a unified data system, and institutionalize shared accountability.